The Effect of Digital Literacy on Students' Learning Outcomes: The Mediating Roles of Learning Motivation and Self-Efficacy - Aini Saputri; Armiati Armiati (Universitas Negeri Padang, 2026)
Enhancing student learning outcomes in the digital age is a primary concern for contemporary vocational education, where digital competence is increasingly vital for scholastic success. This study investigates the influence of digital literacy on Informatics learning outcomes, specifically exploring the mediating roles of learning motivation and self-efficacy. Utilizing a quantitative framework, the research employed a purposive sampling technique to collect data from 102 students enrolled in the Office Management and Business Services (MPLB) and Digital Business and Marketing (BDP) programs at SMK Negeri 2 Bukittinggi. The collected data were analyzed via Structural Equation Modeling–Partial Least Squares (SEM-PLS) using SmartPLS 4.0. Empirical results reveal that digital literacy exerts a direct, positive, and significant effect on Informatics learning outcomes. Furthermore, digital literacy demonstrates a positive influence on both learning motivation and self-efficacy. Notably, both motivation and self-efficacy were found to significantly mediate the connection between digital literacy and academic results. These findings underscore the critical role of digital literacy in academic attainment, suggesting that pedagogical strategies in vocational institutions should incorporate methods that foster psychological engagement to maximize student outcomes in an increasingly digital educational landscape.